PERBANDINGAN ALBENDAZOLE ORAL DENGAN PERMETHRIN 5% KRIM TOPIKAL UNTUK PENGOBATAN SKABIES DI PONDOK PESANTREN AL MUAYYAD SURAKARTA - , Miratri Winny RisAdini; , Dr. dr. Moerbono Mochtar, SpKK. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Scabies has generally known as a common major health problem in a densely populated community, for instance in an Islamic boarding school. Even though, Permethrin 5% cream is a kind of effective therapies preference to eliminate scabies, the acquiescence of the patient, as well as, the accuracy in applying the cream, have become frequent problem to deal with. The current information related to the attainment of albendazole tablet in controlling scabies encouraged to hold this research. Objective: This study compares the efficacy of oral albendazole with topical permethrin cream in the treatment of scabies. Methods: One hundred and two patients with scabies in Al Muayyad Islamic boarding school Surakarta randomly separated into two groups. Scabies diagnostic established after the discovering of scabies mites, eggs, or scibala of the microscopic assessment or in the clinical assessment has found tunnels, papule, pustule, vesicle or excoriation with classic distribution along with itchiness that escalating at night for one who associates with patients with scabies. Fifty children obtained permethrin 5% and the other 52 children obtained albendazole tablet 800 mg/day for 3 days in a row. Evaluation held in the 0 th day and the 14 th day. To equalized the treatment, permethrin group attained amylum tablet for the next 3 days and albendazole group attained bland cream on the first day of treatment. Results: On the 14 th day of evaluation, the cure rate of albendazole had illustrated around 86.54%, meanwhile the cure rate of permethrin 5% had shown about 94% (p>0.05). Furthermore, from the point of view of the quality of life, severity of the lesions, and itchiness reduction, permethrin 5% and albendazole indicated an excellent convenience (p<0.05). Both of the groups did not demonstrate any serious side effects. Conclusion: Albendazole tablet with dosage 800mg/day that given for three consecutive days, are as effective as, topical cream permethrin 5% with minimal side effect.